Sentinel Lymph Node Surgery after Neoadjuvant Chemotherapy in Patients With Node-Positive Breast Cancer: The American College of Surgeons Oncology Group (ACOSOG) Z1071 Clinical Trial - Boughey, Judy C. (2013)
IMPORTANCE: Sentinel lymph node (SLN) surgery provides reliable nodal staging information with less morbidity than axillary lymph node dissection (ALND) for clinically node-negative (cN0) breast cancer patients. The application of SLN surgery for staging the axilla following chemotherapy for women who initially had node-positive breast cancer (cN1) is unclear because of high false negative results reported in previous studies. OBJECTIVE: To determine the false negative rate (FNR) for SLN surgery following chemotherapy in patients initially presenting with biopsy-proven node-positive breast cancer. DESIGN, SETTING, AND PATIENTS: The ACOSOG Z1071 trial enrolled women with clinical T0–4 N1–2, M0 breast cancer who received neoadjuvant chemotherapy. Following chemotherapy, patients underwent both SLN surgery and ALND. SLN surgery using both blue dye and a radiolabeled colloid mapping agent was encouraged. MAIN OUTCOME MEASURE: The primary endpoint was the FNR of SLN surgery after chemotherapy in women who presented with cN1 disease. We examined the likelihood that the FNR in those with 2 or more SLNs examined was greater than 10%, the rate expected for women undergoing SLN surgery who present with clinically node-negative disease. RESULTS: Seven hundred fifty-six patients were enrolled from 136 institutions. Of 663 evaluable patients with cN1 disease, 649 underwent chemotherapy followed by both SLN surgery and ALND. A SLN could not be identified in 46 patients (7.1%). Only one SLN was excised in 78 patients (12.0%). Of the remaining 525 patients with 2 or more SLNs removed, no cancer was identified in the axillary lymph nodes of 215 patients yielding a pathological complete nodal response of 41.0% (95% CI: 36.7%–45.3%). In 39 patients, cancer was not identified in the SLNs but was found in lymph nodes obtained with ALND resulting in a FNR of 12.6% (90% Bayesian Credible Interval, 9.85%–16.05%). CONCLUSIONS AND RELEVANCE: Among women with cN1 breast cancer receiving neoadjuvant chemotherapy who had 2 or more SLNs examined, the FNR was not found to be 10% or less. Given this FNR threshold, changes in approach and patient selection that result in greater sensitivity would be necessary to support the use of SLN surgery as an alternative to ALND. TRIAL REGISTRATION: clinicaltrials.gov; trial identifier NCT00881361.